DSM-5 and ICD-11 criteria for bipolar disorder: Implications for the prevalence of bipolar disorder and validity of the diagnosis - A narrative review from the ECNP bipolar disorders network - Kessing, Lars Vedel; González-Pinto, Ana; Fagiolini, Andrea; Bechdolf, Andreas; Reif, Andreas; Yildiz, Ayşegül; Etain, Bruno; Henry, Chantal; Severus, Emanuel; Reininghaus, Eva Z; Morken, Gunnar; Goodwin, Guy M; et al. (European neuropsychopharmacology, 2021)
This narrative review summarizes and discusses the implications of the Diagnostic and Statistical Manual of Mental Disorders (DSM)-5 and the upcoming International Classification of Diseases (ICD)-11 classification systems on the prevalence of bipolar disorder and on the validity of the DSM-5 diagnosis of bipolar disorder according to the Robin and Guze criteria of diagnostic validity. Here we review and discuss current data on the prevalence of bipolar disorder diagnosed according to DSM-5 versus DSM-IV, and data on characteristics of bipolar disorder in the two diagnostic systems in relation to extended Robin and Guze criteria: 1) clinical presentation, 2) associations with para-clinical data such as brain imaging and blood-based biomarkers, 3) delimitation from other disorders, 4) associations with family history / genetics, 5) prognosis and long-term follow-up, and 6) treatment effects. The review highlights that few studies have investigated consequences for the prevalence of the diagnosis of bipolar disorder and for the validity of the diagnosis. Findings from these studies suggest a substantial decrease in the point prevalence of a diagnosis of bipolar with DSM-5 compared with DSM-IV, ranging from 30-50%, but a smaller decrease in the prevalence during lifetime, corresponding to a 6% reduction. It is concluded that it is likely that the use of DSM-5 and ICD-11 will result in diagnostic delay and delayed early intervention in bipolar disorder. Finally, we recommend areas for future research.
Keywords: Bipolar Disorder; International Classification of Diseases; mezinárodní klasifikace nemocí; prevalence; lidé; Diagnostic and Statistical Manual of Mental Disorders; bipolární porucha; Prevalence; Delayed Diagnosis; Diagnostický a statistický manuál mentálních poruch; Bipolar disorder; DSM-5; ICD-11; Validity of diagnosis; Diagnostic delay; Delayed early intervention; opožděná diagnóza; Humans